To the problem of significance of the parameter «peak height velocity» in puberty as the biomarker of chronobiological status of the population in growth studies - Fedotova Tatiana K.; Gorbacheva Anna K. (Вестник Московского Университета. Серия XXIII: Антропология)
Introduction. The significance of peak height velocity (PHV) in screening studies of children and adolescents as the biomarker of the chronobiological status of the population is in the focus of the study. Material and methods. The analysis embraces a significant specter of samples (N=37, literary data), including different ethnoterritorial groups of Russia and former USSR, examined through the vast historical period of second half of XX century – beginning of the XXI century. The analysis of interpopulation variability of the parameter of peak height velocity of growth changes of the average level of height through the adolescence is under discussion – its absolute value (MPHV, cm) and chronological age (APHV, years); intragroup sexual differences of these characteristics are under consideration as well. Results. Dynamic curves of height increase for urban samples from USSR territory, both native populations and Russian, have dome-shaped form, monotonous height increase/gain velocities up to the peak, slump further on. Traditional Mongolian groups and rural Abkhazian show the dynamic curve with descending wavy form. Histograms of intergroup distribution of the parameter APHV both for boys and girls differ from normal Gaussian distribution and gravitate towards double-peak form. Population values of APHV for boys are two and a half years later as compared to girls; MPHV is a more solid parameter, sex differences here are 0.41 cm with boys’ advantage. Factor analysis revealed definite autonomy of the process of pubertal spurt for male and female adolescents: the first factor describes growth activity of boys, the second — of girls (35% and 30% of the total variability of parameters correspondingly). Conclusion. The results allowed to conclude, that the variability of the parameter points to the significant social/anthropogenic base of chronobiological status of the population and independent growth strategies of male and female sexes, which suggests to interpret PHV as the valid and perspective biomarker in population growth studies.